2021
DOI: 10.3389/fimmu.2021.698578
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient Placental Virus Replication and Absence of Neonatal Cell-Specific Immunity Upon Sars-CoV-2 Infection During Pregnancy

Abstract: Pregnant women have been carefully observed during the COVID-19 pandemic, as the pregnancy-specific immune adaptation is known to increase the risk for infections. Recent evidence indicates that even though most pregnant have a mild or asymptomatic course, a severe course of COVID-19 and a higher risk of progression to diseases have also been described, along with a heightened risk for pregnancy complications. Yet, vertical transmission of the virus is rare and the possibility of placental SARS-CoV-2 infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…Haematogenous spread as a mechanism of infection and transmission across the placenta into the fetal circulation appears unlikely, due to inefficient viral replication in placental tissues. 25 The fetal intestine, directly exposed to the amniotic fluid via fetal swallowing, shows an increase in the expression of ACE2 throughout gestation with a high level of TMPRSS2 expression in the mucosa. Results from publicly available fetal single cell atlas data support our findings, 22 allowing extension of these observations to 8 PCW, before the gestational age that fetal swallowing is known to begin.…”
Section: Discussionmentioning
confidence: 99%
“…Haematogenous spread as a mechanism of infection and transmission across the placenta into the fetal circulation appears unlikely, due to inefficient viral replication in placental tissues. 25 The fetal intestine, directly exposed to the amniotic fluid via fetal swallowing, shows an increase in the expression of ACE2 throughout gestation with a high level of TMPRSS2 expression in the mucosa. Results from publicly available fetal single cell atlas data support our findings, 22 allowing extension of these observations to 8 PCW, before the gestational age that fetal swallowing is known to begin.…”
Section: Discussionmentioning
confidence: 99%
“…Population-level data suggest that rates of SARS-CoV-2 positivity among newborns in SARS-CoV-2-exposed pregnancies range from 1% to 3% [83,[120][121][122][123][124], with placental infection being a relatively rare event. One meta-analysis of case reports and case series estimated the rate of placental infection as 7% [125], although prospective studies have identified even lower rates of placental infection [83,84,126,127]. Protective mechanisms against placental infection include low rates of maternal SARS-CoV-2 viremia, preserved immune defenses at the syncytiotrophoblast border, and the lack of coordinated expression of molecules required for SARS-CoV-2 attachment and entry (ACE2 and TMPRSS2) into the syncytiotrophoblast [80,83,128].…”
Section: Transplacental Transmission Of Sars-cov-2 and Direct Fetal I...mentioning
confidence: 99%
“…There seem to be two potential hypotheses of exosomal contribution in utero, as well as in fetal development: (1) SARS-CoV-2 infections via exosomes, or (2) in utero development of immunity. While exosomes have been found to carry viral RNA, there seems to be little to no viral replication in utero [60]. This observation discards the first hypothesis that exosomes may induce viral infection in utero.…”
Section: Sars-cov-2 and Fetal Development: The Role Of Exosomesmentioning
confidence: 78%
“…While only ~10% infants were found to be positive for COVID-19, most studied infant cases had developed immunoglobulin G and M (IgG, IgM) antibodies against SARS-CoV-2 [59]. In another study, no viral RNA was detected in the placentas of COVID-19 positive pregnant women [60]. Furthermore, there seems to be no confirmed cases of intrauterine infection of SARS-CoV-2 from mothers to their fetuses.…”
Section: Sars-cov-2 and Fetal Development: The Role Of Exosomesmentioning
confidence: 86%
See 1 more Smart Citation